Measuring people's views on health system performance: Design and development of the People's Voice Survey. - Todd P Lewis; Neena R Kapoor; Amit Aryal; Rodrigo Bazua-Lobato; Susanne Carai; Emma Clarke-Deelder; Kevin Croke; Rashmi Dayalu; Laura Espinoza-Pajuelo; Günther Fink; Patricia J Garcia; Ezequiel Garcia-Elorrio; et al. (PLoS Medicine)
Todd Lewis and co-authors discuss development and use of the People's Voice Survey for health system assessment.